Efficacy of central venous catheter in pleurodesis in refractory hepatic hydrothorax - Adel H.A Ghoneim; Mohamed Sobh El Gammal; Mohamed M.N AboZaid; Ahmad Abd El Rahman (Egyptian Journal of Chest Disease and Tuberculosis, 2019)
Background Hepatic hydrothorax is an important complication of cirrhosis and portal hypertension. Recurrent hepatic hydrothorax may be difficult to manage. In cases where medical therapies, usually diuretics, have failed to adequately control symptomatic effusion, thoracentesis, thoracostomy tube drainage, and pleurodesis have been employed. Tunneled pleural catheters are used for control and long-term management of recurrent pleural effusions. The aim of management of recurrent effusion in patients with hepatic hydrothorax is to relieve symptoms, to decrease discomfort of the patient through repeated aspiration, and chemical pleurodesis to prevent recurrence. Intrapleural chemical agents including tetracycline, doxycycline, bleomycin, talc insufflations, or talc slurry are used for pleurodesis. Tetracycline is the most common agent. A central venous catheter is a thin, long flexible tube that may be inserted into the pleural space. Objectives The aim of this study is to explore the efficacy, safety, and tolerability of central venous catheter in pleurodesis by tetracycline to relieve distressing symptoms and prevent fluid re-accumulation in patients with recurrent hepatic hydrothorax. Patients and methods This study recruited 22 patients with hepatic hydrothorax to evaluate the effectiveness of the small-bore central venous line in draining the pleural cavity as well as to evaluate the effectiveness of the intrapleural tetracycline as a sclerosing agent. Results Regarding the success rate of pleurodesis in the studied patients, the procedure was successful in 16 (72.7%) cases and failed in six (27.3%) cases. Regarding the reported complications, chest pain was the most commonly reported complication followed by dyspnea, fever, and tachycardia. Conclusion Central venous catheters are small and flexible and allow the patients to move easily offering a wonderful, comfortable, and tolerable method for drainage and pleurodesis.